Bilingual Advantage in Reading Comprehension: Strategic Reading Behaviors among Indonesian Pre-Service Teachers - Heryatun, Yayu; Oktaviana, Fadilla (English Education, Linguistics, and Literature Journal, 2026)
This study investigates differences in English reading comprehension and strategic reading behaviour between monolingual and bilingual Indonesian pre-service teachers. Situated in a multilingual English as a Foreign Language (EFL) context, the study addresses how students’ language backgrounds may shape their ability to process English texts, use comprehension strategies, and respond to higher-order reading tasks. A qualitative comparative design was employed with 12 six-semester undergraduate students from a department at one state Islamic university in Banten. Participants were purposively grouped into six monolingual and six bilingual students based on their self-reported language-use profiles. Data were collected through a language-background questionnaire, TOEFL-based reading tasks, and semi-structured interviews. The data were analysed thematically by comparing recurring patterns in participants’ strategy use, reported reading difficulties, and comprehension performance. The findings indicate that bilingual students showed stronger strategic flexibility than monolingual students, particularly in skimming, scanning, vocabulary inference, and activation of prior knowledge. Bilingual participants were also more likely to connect information across languages and use their linguistic repertoire to support comprehension. Monolingual participants tended to rely on linear reading and word-by-word translation, which often slowed comprehension. However, both groups experienced difficulty with main-idea and inference questions, indicating the need for explicit instruction in higher-order comprehension strategies. The study concludes that bilingualism may provide cognitive and strategic resources that support second-language reading, but these advantages require pedagogical support to become effective academic reading skills.